Sarcoplasmic Reticulum Calcium Release Is Required for Arrhythmogenesis in the Mouse - Edwards, Andrew G.; Mørk, Halvor; Stokke, Mathis K.; Lipsett, David B.; Sjaastad, Ivar; Richard, Sylvain; Sejersted, Ole M.; Louch, William E. (Frontiers in Physiology, 2021)
Dysfunctional sarcoplasmic reticulum Ca2+ handling is commonly observed in heart failure, and thought to contribute to arrhythmogenesis through several mechanisms. Some time ago we developed a cardiomyocyte-specific inducible SERCA2 knockout mouse, which is remarkable in the degree to which major adaptations to sarcolemmal Ca2+ entry and efflux overcome the deficit in SR reuptake to permit relatively normal contractile function. Conventionally, those adaptations would also be expected to dramatically increase arrhythmia susceptibility. However, that susceptibility has never been tested, and it is possible that the very rapid repolarization of the murine action potential (AP) allows for large changes in sarcolemmal Ca2+ transport without substantially disrupting electrophysiologic stability. We investigated this hypothesis through telemetric ECG recording in the SERCA2-KO mouse, and patch-clamp electrophysiology, Ca2+ imaging, and mathematical modeling of isolated SERCA2-KO myocytes. While the SERCA2-KO animals exhibit major (and unique) electrophysiologic adaptations at both the organ and cell levels, they remain resistant to arrhythmia. A marked increase in peak L-type calcium (ICaL) current and slowed ICaL decay elicited pronounced prolongation of initial repolarization, but faster late repolarization normalizes overall AP duration. Early afterdepolarizations were seldom observed in KO animals, and those that were observed exhibited a mechanism intermediate between murine and large mammal dynamical properties. As expected, spontaneous SR Ca2+ sparks and waves were virtually absent. Together these findings suggest that intact SR Ca2+ handling is an absolute requirement for triggered arrhythmia in the mouse, and that in its absence, dramatic changes to the major inward currents can be resisted by the substantial K+ current reserve, even at end-stage disease.